In vivo evaluation of compliance mismatch on intimal hyperplasia formation in small diameter vascular grafts. (21st March 2023) - Yao, Yuan; Pohan, Grace; Cutiongco, Marie F. A.; Jeong, YeJin; Kunihiro, Joshua; Zaw, Aung Moe; David, Dency; Shangguan, Hanyue; Yu, Alfred C. H.; Yim, Evelyn K. F.
Abstract : Synthetic vascular grafts with varied compliance were fabricated and studied in vivo . Reducing compliance mismatch between graft and native artery lowered intimal hyperplasia formation and increased graft patency. Abstract : Small diameter synthetic vascular grafts have high failure rate due to the thrombosis and intimal hyperplasia formation. Compliance mismatch between the synthetic graft and native artery has been speculated to be one of the main causes of intimal hyperplasia. However, changing the compliance of synthetic materials without altering material chemistry remains a challenge. Here, we used poly(vinyl alcohol) (PVA) hydrogel as a graft material due to its biocompatibility and tunable mechanical properties to investigate the role of graft compliance in the development of intimal hyperplasia and in vivo patency. Two groups of PVA small diameter grafts with low compliance and high compliance were fabricated by dip casting method and implanted in a rabbit carotid artery end-to-side anastomosis model for 4 weeks. We demonstrated that the grafts with compliance that more closely matched with rabbit carotid artery had lower anastomotic intimal hyperplasia formation and higher graft patency compared to low compliance grafts. Overall, this study suggested that reducing the compliance mismatch between the native artery and vascular grafts is beneficial for reducing intimal hyperplasia formation.